Application of Soil Conservation Service Curve Number model for deriving rainfall runoff relationship in an ungauged watershed of mountain region - KARTHIK, GANGANNAGARI; NAGARAJAN, K.; MANIVANNAN, S.; KANNAN, BALAJI (Journal of Soil and Water Conservation, 2023)
Rainfall and runoff relationship is one of the key inputs required for assessing available water for planning watershed interventions. It is tedious to establish the rainfall and runoff relationship for an ungauged watershed, particularly in the hilly terrains. However, Soil Conservation Service (SCS) Curve Number method is well established equation and applied globally for estimating runoff. Hence, an attempt is made to derive the rainfall and runoff relationship using the SCS Curve Number coupled with the Google Earth Engine (GEE) in Nanjannad hill watershed of the Nilgiris district of Tamil Nadu. The monthly and annual rainfall and runoff analysis for the period of 14 years (2008–2021) showed that the October and November had the highest rainfall and runoff. The rainfall is varied between 880 mm and 1860 mm and the runoff ranged from 148 mm to 345 mm. The average annual runoff of 14 years period was observed as 249 mm (17.1%) and the maximum percentage of rainfall to runoff was estimated as 22.66% in the year 2009, the relationship between rainfall and runoff exhibited the positive correlation (R2 = 0.79). Accordingly, the total water available for harvesting annually stood at 1.08 Mcm in Nanjannad watershed. Hence, it is suggested that, watershed interventions can be planned to manage the 17 to 22% annual rainfall and rainfall and runoff relationship for watershed planning can be considered as 0.17 to 0.22.